PERTUMBUHAN DAN LAJU EKSPLOITASI KERANG KEPAH (Meretrix sp.) DI MUARA SUNGAI ASAHAN DESA BAGAN ASAHAN KABUPATEN TANJUNG BALAI ASAHAN - Tri Hartati uyun Matondang; Ipanna Enggar Susetya (AQUACOASTMARINE, 2018)
Asahan River is the catching area of shellfish which is the main source of income for fishermen. One shellfish caught is Kepah Shell (Meretrix sp.). The purpose of this study was to determine the pattern of growth and the rate of exploitation of Kepah Shell. The research method used is purposive sampling method. The research was done of April until May 2018. The shells obtained consisted of three stations with a total total of 1516. The results showed that the frequency of the shell length was 10-47 mm. The growth pattern of Kepah Shell is allometric negative. The condition factor on station I was 0,09 average, station II averaged 0,12 and station III averaged 0,12. The result of parameter analysis of Kerang Kepah growth consist of growth coefficient (K) that is 1,4 year, infinitive length (L∞) is 45,15 mm, theoretical age of shell at the same length equal to zero (t0) that is -0,10. Analysis of alleged mortality and exploitation rate of Kepah Shell consisting of total mortality (Z) is 5,823/year, natural mortality (M) is 2.015/year, capture mortality (F) is 3,808/year, and rate exploitation (E) is 0.6 (overfishing).Kata Kunci : Muara Sungai Asahan, Kerang Kepah (Meretrix sp.), Pertumbuhan, Laju Eksploitasi